Human tissue and global ethics - Dickenson, Donna (Henry Stewart Talks, 2015)
The global trade in human tissue, Regulation of human tissue trade, The body as property, Case studies, Giving or selling eggs, Two alternatives for the future
Archived at 2022/02/28